Immunohistochemical characteristic of proliferative and apoptotic processes in testicular seminoma. - Potapov, S. M.; Markovskyi, V. D.; Galata, D. I.; Pliten, O. M.; Gorgol, N. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Testicular tumors are rare neoplasia (1-2% of all malignant tumors in men) and are more common in young men, what attaches importanceof this problem both medical and social significance. Objective. The aim of the work was to study proliferative and apoptotic processes in testicular seminoma. Methods. The study was performed on 13 surgically removed testicles affected by seminoma.Tumors were grouped according to the degree of tumorous progression in accordance with the pTNM classification. For evaluation of proliferative and apoptotic processes the relative area (S) and intensity (L) of Ki-67, Bax, Bcl-2, and p53 expression were studied. The proliferation index (PI) was calculated as well. Results. The study determined increasing of average S, L values of Ki-67 expression and PI, and also very high and moderate positive correlation between PI and S with L expression (r= +0,98; r= +0,60; p<0,05, respectively) during the transition from the initial to the late stages of tumorous progressionwas revealed. S of Bax expression was also increasing at the transition from early to late stages of tumorous progression, and L expression remained high regardless of stage. High positive correlation between S of Bax and S of Ki-67 expression and between S of Bax and PI (r= +0.83; r= +0.84; p<0.05, respectively) was revealed during the transition from the initial to the late stages of tumorous progression. This result allows us to talk about the lack of resistance of seminoma tumorous cells to apoptosis. The activity of the anti-apoptotic protein bcl-2 in the seminoma was extremely insignificant, and p53 expression was absent, which together indicates a low tumor aggressiveness. Conclusion. Based on the foregoing we believe that in the diagnosis of testicular tumors it is appropriate to use Ki-67, Bax, bcl-2 and p53, as reflecting the malignant potential of the tumor and as prognostic markers. In the same time we have opinion that increasing of S of Bax expression during the transition from the initial to the late stages of tumorous progression in combination with p53 intactness characterizes seminoma as curable tumor with lowaggressiveness.